THE EFFECT OF PASSIVE RANGE OF MOTION (ROM) ON IMPROVEMENT OF MUSCLE STRENGTH IN PATIENTS STROKE AT THE GRANDMED HOSPITAL LUBUK PAKAM IN 2023 - Wati, Syatria; Febriana, Sanya; Hayati, Kardina; Hijriana, Isni (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Stroke is a disease that can cause disability in the body. As many as 30% of stroke sufferers become permanently disabled. Stroke occurs when blood vessels in the brain fail to provide oxygen to brain cells. If brain cells do not have enough oxygen, then brain cells become damaged. The pre-experimental research design uses a one group pre-post test research design where the experimental group first assesses their muscle strength, then is given treatment and measured again. The sample was determined using Accidental Sampling, namely by chance with a sample size of 21 patients. Before being given Passive ROM, muscle strength was paralyzed in 3 respondents (14.3%), weakness in 8 respondents (38.1%), and moderate weakness in 10 respondents (47.6%). After being given passive ROM, there was an increase in muscle strength in value 1 for 3 people (14.3%), value 2 for 8 people (38.1%), and value 3 for 10 people (47.6%). Based on data analysis, a significant value of 0.00 (? 0.05) was obtained, which means that there was an influence before and after being given passive ROM on the muscle strength of stroke patients at Grandmed Lubuk Pakam Hospital in 2023.